REKONSTRUKSI PRINSIP SYARIAH PADA SMART CONTRACT ETHEREUM: ANALISIS KEABSAHAN IJAB-QABUL OTOMATIS ERA SOCIETY 5.0 - Sari, Muspita; Kurniati, Kurniati; Misbahuddin, Misbahuddin; Darliana, Darliana (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2026)
This article examines the validity of ijab-qabul in Ethereum-based smart contracts and reconstructs classical contract concepts within the framework of contemporary Islamic law in the Society 5.0 era. It focuses on how principles of fiqh muamalah—such as mutual consent (taradhi), clarity (al-wuduh), and the absence of gharar—can adapt to automated contract systems. The study employs a normative-conceptual approach through library research, drawing on classical fiqh literature, contemporary Islamic legal studies, and technical smart contract documents, analyzed descriptively, comparatively, and through a maqasid al-shariah perspective. The findings indicate that smart contracts structurally fulfill the essential elements and conditions of a valid contract but face challenges regarding free will, intention (qasd), and limited corrective mechanisms such as khiyar. While enhancing transparency and legal certainty, they also pose risks of injustice due to assumed consent, digital literacy gaps, and insufficient consumer protection. The novelty of this study lies in reconstructing ijab-qabul as a digitally validated expression of intent rather than a purely verbal one. The study highlights the need for ethical smart contracts, adaptive regulation, and strengthened digital literacy to ensure alignment with justice, public interest, and consumer protection within Islamic law.